Assessing cognitive performance in badminton players: A reproducibility and validity study - van de Water, T.; Huijgen, B.; Faber, I. R.; Elferink-Gemser, M. (Journal of Human Kinetics, 2017)
Fast reaction and good inhibitory control are associated with elite sports performance. To evaluate the reproducibility and validity of a newly developed Badminton Reaction Inhibition Test (BRIT), fifteen elite (25 ± 4 years) and nine non-elite (24 ± 4 years) Dutch male badminton players participated in the study. The BRIT measured four components: domain-general reaction time, badminton-specific reaction time, domain-general inhibitory control and badminton-specific inhibitory control. Five participants were retested within three weeks on the badminton-specific components. Reproducibility was acceptable for badminton-specific reaction time (ICC = 0.626, CV = 6%) and for badminton-specific inhibitory control (ICC = 0.317, CV = 13%). Good construct validity was shown for badminton-specific reaction time discriminating between elite and non-elite players (F = 6.650, p < 0.05). Elite players did not outscore non-elite players on domain-general reaction time nor on both components of inhibitory control (p > 0.05). Concurrent validity for domain-general reaction time was good, as it was associated with a national ranking for elite (p = 0.70, p < 0.01) and non-elite (p = 0.70, p < 0.05) players. No relationship was found between the national ranking and badminton-specific reaction time, nor both components of inhibitory control (p > 0.05). In conclusion, reproducibility and validity of inhibitory control assessment was not confirmed, however, the BRIT appears a reproducible and valid measure of reaction time in badminton players. Reaction time measured with the BRIT may provide input for training programs aiming to improve badminton players` performance.